2012
DOI: 10.1172/jci61248
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ER stress and mTORC1 suppresses hepatic sortilin-1 levels in obese mice

Abstract: Recent GWAS have identified SNPs at a human chromosom1 locus associated with coronary artery disease risk and LDL cholesterol levels. The SNPs are also associated with altered expression of hepatic sortilin-1 (SORT1), which encodes a protein thought to be involved in apoB trafficking and degradation. Here, we investigated the regulation of Sort1 expression in mouse models of obesity. Sort1 expression was markedly repressed in both genetic (ob/ob) and high-fat diet models of obesity; restoration of hepatic sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 57 publications
10
103
0
Order By: Relevance
“…Our current study also reveals a previously unrecognized function of SORT1 in regulating LDLR protein levels in hepatocytes. This finding is consistent with recent reports demonstrating that SORT1 deficiency leads to increased plasma LDL cholesterol, 29,40 and provides an additional mechanism that may contribute to this outcome. In addition, our results may also provide an explanation why genetic ablation or silencing of SORT1 resulted in a less pronounced increase in plasma LDLcholesterol on a Ldlr −/− background.…”
Section: Discussionsupporting
confidence: 93%
“…Our current study also reveals a previously unrecognized function of SORT1 in regulating LDLR protein levels in hepatocytes. This finding is consistent with recent reports demonstrating that SORT1 deficiency leads to increased plasma LDL cholesterol, 29,40 and provides an additional mechanism that may contribute to this outcome. In addition, our results may also provide an explanation why genetic ablation or silencing of SORT1 resulted in a less pronounced increase in plasma LDLcholesterol on a Ldlr −/− background.…”
Section: Discussionsupporting
confidence: 93%
“…Palmitate is a strong inducer of ER stress in hepatocytes ( 34 ). One recent study reports that sort1 gene transcription is repressed in obese mice by mechanisms involving activation of ER stress, mTORC1, and an ER stress-induced transcriptional factor ATF3 ( 35 ). Our results showed decreased hepatic Sort1 mRNA in Western diet-fed mice but not in ob / ob mice or in human steatotic livers.…”
Section: Discussionsupporting
confidence: 48%
“…This effect of insulin on LDLR protein expression is mediated in part by mTORC1 activity (34). In addition, mTORC1 activity represses sortillin 1, which in addition to apoB metabolism, contributes to VLDL-TAG export (35). In this study, we identified another major role of mTORC1 in the regulation of lipid export and neutral lipid content in liver.…”
Section: Discussionmentioning
confidence: 68%